تحولات تعليم اللغة العربية في أمريكا واليابان وألمانيا ومقارنتها بأساليب التعليم في إيران - ساروكلايى, ذلفا معیل; فرزانه, سيد بابك; تبار, مرضية قلي (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2023)
Teaching Arabic language has always had its own special features and difficulties among all scientific fields. Due to the existence of these difficulties and complications, scholars in this field have always been searching for new theories, methods and tools to improve and optimize its teaching. This research aims to achieve a model for the proper learning of Arabic language by examining and introducing the most important methods and models of teaching Arabic as a second language in different countries and comparing them with each other. The research also seeks to know to what extent the Arabic language education centers have used advanced education tools to achieve the mentioned goal. The results obtained from the research indicate that learning the Arabic grammar and the correct structure of phrases and sentences and the correct transfer of concepts are essential, but if these trainings are carried out without paying enough attention to increasing the language ability, it will not lead to the learning of the language in a desirable way. By examining the educational methods in different countries, we came to the conclusion that grammar cannot be a suitable solution for education, and the phenomenon that has made learning Arabic difficult is diglossia, and different methods are used in the world to teach Arabic as a second language and its practical use. It is taken that we will introduce them in this article: it is worth mentioning that in all this method, learning the language in the traditional way and focusing on the grammar is ignored. يهدف هذا البحث إلى مقارنة أهم أساليب وأنماط تعليم اللغة العربية بصفتها اللغة الرسمية الثانية في العديد من الدول، ومقارنتها مع بعضها البعض للوصول إلى نمط لاکتساب هذه اللغة بشكل سليم ومتقن. وفي هذا الصدد يسعى البحث إلى معرفة مدى استخدام مراكز تعليم اللغة العربية لأدوات التعليم المتقدمة لتحقيق الهدف المذكور. وتوصل البحث إلى أن تعلم قواعد اللغة العربية والاستعمال السليم للعبارات والجمل، وكذلك النقل السليم للمفاهيم يُعد أمراً ضرورياً، ولكن القيام بهذا التعليم دون الاهتمام الكافي بزيادة القدرة اللغوية، فإنه لن يؤدي إلى اکتساب اللغة بالشكل المطلوب. ومن خلال مراجعة الأساليب التعليمية في البلدان المختلفة، فقد ظهر أن التعليم وفق القواعد النحوية لن تكون الأسلوب المناسب للتعليم، والظاهرة التي تجعل اکتساب اللغة العربية أمراً بالغ الصعوبة هي ازدواجية اللغة. ويجري الاستعانة بأساليب مختلفة في بلدان العالم لتعليم اللغة العربية كلغة ثانية واستخدامها العملي والتطبيقي، وستتم الإشارة إلى هذه الأساليب في هذه الدراسة. وتجدر الإشارة إلى أن في جميع هذه الأساليب يُعتمد على تعليم اللغة بطريقة تقليدية ولم يتم التركيز فيها على القواعد النحوية.